Dezmosomi - stabilni, a dinamični medcelični stiki - Resnik, Nataša (Medicinski razgledi, 2008)
Desmosomes are the strongest cell junctions. They are especially abundant in tissues such as the epithelium and the cardiac muscle, which are subject to mechanical stress. A desmosome consists of two desmosomal halves, which contain a transmembrane region for intercellular binding and a cytosolic plaque region that anchors intermediate filaments. The intermediate filament network in adjacent cells distributes spot loads on the tissue across the entire surface, thereby reducing the risk of tissue injury. The desmosome dynamics are controlled by changes in extracellular Ca2+ concentrations, phosphorylation of desmosomal proteins and the activity of enzymes which proteolytically cleave desmosome proteins. Splitting of desmosomal halves leads to the transport of desmosomal proteins into the lysosomes or non-lysosomal compartments. Desmosomal proteins from de novo synthesis and from cytosolic pools of desmosomal proteins enable the assembly of new desmosomes. These dynamic attributes of desmosomes are important prerequisitesfor the acquisition and maintenance of tissue homeostasis during morphogenesis, embryogenesis and tissue differentiation. Desmosomes are weakened either by autoantibodies, bacterial toxins or mutations, causing desmosomal diseases. In this review, desmosomes are portrayed as stable and dynamic structures that are subject to mechanical and physiological changes.
Keywords: Desmosomes; Dezmosomi; Bakterijski toksini; Pathology; Physiology; Avtoimunske bolezni; Autoimmune Diseases; Dedne bolezni; tumor; Novotvorbe; Bacterial Toxins; citologija; Hereditary Diseases; medcelični stik; Neoplasms